Application of Quality by Design Approach to Bioanalysis: Development of a Method for Elvitegravir Quantification in Human Plasma. Issue 5 (October 2017) - Baldelli, Sara; Marrubini, Giorgio; Cattaneo, Dario; Clementi, Emilio; Cerea, Matteo
Abstract : Background: The application of Quality by Design (QbD) principles in clinical laboratories can help to develop an analytical method through a systematic approach, providing a significant advance over the traditional heuristic and empirical methodology. In this work, we applied for the first time the QbD concept in the development of a method for drug quantification in human plasma using elvitegravir as the test molecule. Methods: The goal of the study was to develop a fast and inexpensive quantification method, with precision and accuracy as requested by the European Medicines Agency guidelines on bioanalytical method validation. The method was divided into operative units, and for each unit critical variables affecting the results were identified. A risk analysis was performed to select critical process parameters that should be introduced in the design of experiments (DoEs). Different DoEs were used depending on the phase of advancement of the study. Results: Protein precipitation and high-performance liquid chromatography–tandem mass spectrometry were selected as the techniques to be investigated. For every operative unit (sample preparation, chromatographic conditions, and detector settings), a model based on factors affecting the responses was developed and optimized. The obtained method was validated and clinically applied with success. Conclusions: To the best of our knowledge, this is the first investigation thoroughly addressing the application of QbD to the analysis of a drug in a biological matrix applied in a clinical laboratory. The extensive optimization process generated a robust method compliant with its intended use. The performance of the method is continuously monitored using control charts. Abstract : Supplemental Digital Content is Available in the Text.